Development of Grinding Wheels for Tools Manufacturing - Lukovics, Imrich; Bílek, Ondřej; Holemý, Stanislav (Manufacturing Technology Journal, 2010)
This paper deals with the possibility of using sintered corundum of grinding tool parts. It assesses the impact of technological conditions on cutting forces during grinding, the tool wear and the quality of machined surfaces, provided changes in concentrations of grains in sintered corundum grinding wheel.
Keywords: Grinding; Sintered Corundum; Cutting Forces; Quality